Perbandingan Kepuasan Mahasiswa pada Pelaksanaan Kuis dengan Metode Konvensional dan Kahoot! Aplikasi - Ferdinan Sihombing; Yuanita Ani Susilowati; Elizabeth Ari Setyarini (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; quizzes are needed to increase student motivation to learn and assess their understanding of the course material. Quizzes can take the form of conventional tests (paper-based tests) and can use information technology, for example, the "Kahoot!" Application. Objective; find out the differences in student satisfaction with the implementation of the Family Nursing quiz with conventional methods and the Kahoot quiz! Application. Method: This is a quasi-experimental study with a two-group posttest only design. The data analysis process used the Shapiro-Wilk normality test and the Mann-Whitney test. Result; indicates the average score of satisfaction obtained at Kahoot! was 7.74 ± 1.873 and the mean in the conventional group was 7.44 ± 1.450. This shows the subject of Kahoot! has a higher satisfaction score than the conventional group subject, and obtained p-value = 0.295 which means there is no significant difference between student satisfaction scores in the Kahoot group! and conventional. Conclusion: There is no significant difference between student satisfaction scores in Kahoot! and convex.